Integrated nutritional garden innovation using vertiminaponic method and PROSA-HI as an effort to prevent stunting in Ngalang Village - Tri Sunarsih; Endah Puji Astuti; Bambang Retnoaji; Elvika Fit Ari Shanti; Ekawati Ekawati (Community Empowerment, 2023)
Ngalang Village is one of the villages in Gedangsari District, Gunung Kidul Regency with a high stunting rate (short and very short) of 28.23%. Nutrition is one of the important factors that determine the level of health of physical and mental development. This is important because it concerns the quality of Indonesia's human resources in the future. The purpose of this program is to improve nutritional status as well as maternal and child health through innovative integrated nutrition gardens using the vertiminaponic method and technology-based PROSA-HI in Ngalang Village. The method that will be applied in this community service activity consists of implementing the PROS-HI innovation, integrated nutrition garden innovation with the vertiminaponic method and evaluating activities. The results of this activity showed an increase in the participants' understanding of the material presented (p value = 0.000). In general, vertiminaponics can solve the nutritional problem of stunting toddlers.